2008
DOI: 10.3928/01484834-20080301-07
|View full text |Cite
|
Sign up to set email alerts
|

Students' Opinions About and Expectations of Effective Nursing Clinical Mentors

Abstract: Nursing practice is an integral part of nursing education in which clinical mentors play an important role. Mentors' attitudes, experience, and knowledge influence nursing students and help them to complete their nursing practice with success. The purpose of this qualitative study was to determine nursing students' opinions about and expectations of effective nursing clinical mentors. Focus group interviews were used to obtain data from 24 students after completion of their third year of nursing school. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 21 publications
(40 reference statements)
2
44
0
17
Order By: Relevance
“…Elcigil and Sari (2008) found a similarity in their study where students viewed the SWN's primary role as one in which they identify deficits and provide knowledge and opportunities tailored to the student. Tensions can arise when the teaching and learning practices of the tertiary setting, where students are the central focus, interact with the clinical environment, where the primary responsibility and focus of registered nurses is to the patient.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Elcigil and Sari (2008) found a similarity in their study where students viewed the SWN's primary role as one in which they identify deficits and provide knowledge and opportunities tailored to the student. Tensions can arise when the teaching and learning practices of the tertiary setting, where students are the central focus, interact with the clinical environment, where the primary responsibility and focus of registered nurses is to the patient.…”
Section: Discussionmentioning
confidence: 82%
“…Gunther (2011, p243) states that students can view the relationship with their SWN 'as the most crucial influence on their professional growth and development'. Such assertions are supported by Elcigil and Sari (2008), who posit SWNs have a key role in the success of the student in the clinical environment. What is not documented in student responses in this study is attempts or otherwise made by students in order to establish or maintain relationships.…”
Section: Discussionmentioning
confidence: 86%
“…(b) Personality traits (7 items) are the emotional tendencies and character traits that include the ability to control their temper and exhibit patience, treat students sincerely, show empathy toward students, and have an enthusiastic attitude in clinical teaching [21]. (c) Teaching ability (13 items) is the process of transmission of skills and attitudes; the creation of an environment that enables learning [26]. It includes instructional skills, creating a positive learning environment, and promoting learning [25], (d) Nursing competence (9 items) is the clinical instructor's theoretical and clinical knowledge used during practice, including the instructor's attitude toward the profession [27] and (e) Evaluation (7 items) is the type and amount of feedback the student receives from the teacher in relation to clinical performances and written assignments.…”
Section: Toolmentioning
confidence: 99%
“…Clinical nursing mentors' attitudes, experience and knowledge were said to influence nursing students' experience [25] , and the student nurses, in particular, are unlikely to have constructed such image of the mentor role in isolation, rather against the backdrop of their shared understanding, practice and experience of working with clinical mentors, suggesting that clinical nurse mentors' attitudes, teaching style and feedback may have significant impacts on shaping the future patient safety behaviours of their students. A qualitative study in Turkey investigated the pre-registration nursing students' views of their clinical mentors [26] . The findings suggested that feedback from mentors was important and that mentors should be motivational, not critical, when providing feedback to the students.…”
Section: Discussionmentioning
confidence: 99%